The Issue of Age and Language Transfer in Second Language Acquisition (Philologia, 2021)
The purpose of this paper is to contribute to second language acquisition research by exploring the age effects in the initial stages of second language (L2) development with respect to the mother tongue transfer of morphosyntactic features. It assumes the generative framework of grammar and language acquisition, where direct L2 child- adult comparison has been a neglected area of research. The [± strong] Infl parameter of Universal Grammar, V-raising in particular, is taken as the linguistic element of investigation, since it assigns different values in English [- strong] and in Macedonian [+ strong]. The participants in the experiment were a group of children (age 8-11) and a group of adults (age 20-60), all native speakers of Macedonian and beginners of L2 English. They were tested after a four-week exposure to specifically designed instruction on English V-raising. As the entire L1 grammar transfers, the results offer support for the Conservation Hypothesis for L1 transfer for the initial stages of second language acquisition (Van de Craats et al. 1999).
Keywords: age effects; language transfer; initial stages; second language acquisition of English; V-raising